Improving clinical care for women with endometriosis: qualitative analysis of women's and health professionals' views - Heather J. Rowe; Karin Hammarberg; Sarah Dwyer; Renea Camilleri; Jane RW Fisher (Taylor & Francis Group, 2021)
Purpose Endometriosis is a chronic condition where endometrial-like cells proliferate outside the uterus causing pain and disability. Limited treatments are available but symptom management is essential for social and economic participation. The aim was to compare women's and health professionals' perceptions of quality of endometriosis health care and opportunities for improvements. Methods Women participated in closed moderated online discussion groups and health professionals in semi-structured telephone interviews. Discussion group text and interview transcripts were thematically analyzed using the Framework Analysis approach. Results Forty-six women, 12 general practitioners (GPs), and 1 gynecologist participated. Endometriosis can have debilitating consequences. However, women reported that healthcare providers may dismiss symptoms, lack essential knowledge and provide inconsistent advice; treatments are seldom successful or without adverse side-effects. Health professionals acknowledged limitations in expertise, persistent myths, and challenges in achieving best practice. Enhancing collaborative care skills, individualized treatment plans, and local referral pathways to multi-disciplinary care may improve satisfaction with endometriosis care-giving and receiving. Conclusions This is the first comparison of patient and practitioner perceptions of endometriosis in primary healthcare. Models of multi-disciplinary, collaborative care need to be developed and evaluated against consumer-informed measures of women's wellbeing, quality of life and satisfaction with symptom management and health care.